Effect of stroke rate reduction on swimming technique during paced exercise - Alberty, M. R.; Potdevin, F. P.; Dekerle, J.; Pelayo, P. P.; Sidney, M. C. (The Journal of Strength and Conditioning Research, 2011)
The purpose of this study is to analyze the acute adaptations of motor organization subsequent to a reduction in spontaneous stroke rate (SR) at different swimming speeds, a task constraint that is currently used by trainers to improve stroke technique. Ten well-trained swimmers (8 males and 2 females, whose mean swimming speed on a 400-m front crawl stroke represents 76.8 ± 3.7% and 73.3 ± 2.7% of the mean speed of the short-course pool world record, respectively) performed 3 sets of 3 time to exhaustion trials in front crawl at paces corresponding to 95%, 100%, and 110% of the mean speed measured in a 400-m race. During the first set, individual SR was continuously recorded and averaged. During the second set (Fixed), participants were constrained to swim at their individual corresponding SR. For the third set (Lowered), an individual corresponding SR value lowered by 5% was imposed. Durations of trials and arm stroke phases durations were analyzed. The results showed that the durations of the whole trials declined significantly from the Fixed set to the Lowered set (p < 0.05). Swimmers spent more time in the nonpropulsive phases (increases ranged from 8.6-13.2%; p < 0.05), and the duration of the propulsive phases did not differ significantly in the lowered set. The significant decline in exercise durations might have been caused by an unusual muscular solicitation. Swimming technique changes during trials in the Fixed set suggest an increase in magnitude and efficiency in the propulsive force and a better body streamlining to limit an increase of the resistive impulse in between arm propelling actions. In conclusion, these results should be taken into account to better define training-set technical benefits and better include the impact of such task constraints into the training schedule.